2006
DOI: 10.1073/pnas.0606843103
|View full text |Cite
|
Sign up to set email alerts
|

A backbone-based theory of protein folding

Abstract: Under physiological conditions, a protein undergoes a spontaneous disorder º order transition called "folding." The protein polymer is highly flexible when unfolded but adopts its unique native, three-dimensional structure when folded. Current experimental knowledge comes primarily from thermodynamic measurements in solution or the structures of individual molecules, elucidated by either x-ray crystallography or NMR spectroscopy. From the former, we know the enthalpy, entropy, and free energy differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
425
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(450 citation statements)
references
References 124 publications
20
425
1
4
Order By: Relevance
“…11,12 This provides the basis of a universal mechanism for osmolyte-mediated protein stabilization by protecting osmolytes and destabilization by urea as the protein backbone is shared by all proteins, regardless of side chain sequence. [13][14][15] The evaluation of group transfer free energy values defined the now classic Tanford model for ureainduced protein denaturation. 16,17 In that model, the thermodynamic interaction of the side chains with the urea solution gave rise to the long held concept of favorable urea interaction with hydrophobic groups as a driving force in urea's denaturation effect.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 This provides the basis of a universal mechanism for osmolyte-mediated protein stabilization by protecting osmolytes and destabilization by urea as the protein backbone is shared by all proteins, regardless of side chain sequence. [13][14][15] The evaluation of group transfer free energy values defined the now classic Tanford model for ureainduced protein denaturation. 16,17 In that model, the thermodynamic interaction of the side chains with the urea solution gave rise to the long held concept of favorable urea interaction with hydrophobic groups as a driving force in urea's denaturation effect.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,22 Our analysis is not at odds with this view, but we believe the picture is more detailed and subtle than often portrayed. Recently, others have demonstrated that, for the a-helix in particular, the classical model of NCIs may not always be appropriate.…”
Section: Discussionmentioning
confidence: 71%
“…21,22 In their hydrogen-bonding hypothesis, Fleming and Rose argue that all potential backbone hydrogen-bond donors and acceptors are satisfied a significant fraction of the time, either via intramolecular hydrogen bonds or hydrogen bonds to water. 23 The basis of the hypothesis is that unsatisfied hydrogen-bonding potential is highly unfavorable energetically and therefore rare.…”
Section: Introductionmentioning
confidence: 99%
“…The fibrillization process is driven by protein backbone interactions; the protein backbone being a feature common to all proteins [26]. It is the hydrogen bonds within the backbone that drive this folding (or misfolding) process [27].…”
Section: Discussionmentioning
confidence: 99%